The transverse musculo‐cutaneous gracilis flap for breast reconstruction: How to avoid complications. Issue 1 (2nd March 2015) - Bodin, Frédéric; Dissaux, Caroline; Dupret‐Bories, Agnes; Schohn, Thomas; Fiquet, Caroline; Bruant‐Rodier, Catherine
Abstract : Background: The transverse musculocutaneous gracilis (TMG) flap has become a common solution for breast reconstruction. However, the safe skin paddle limits are not yet understood. In this study, we attempted to address this issue based on our experiences with inferior and posterior skin paddle extension. Methods: Forty‐four breast reconstructions with TMG flaps performed between November 2010 and January 2014 were analyzed retrospectively. For the first 20 cases, the flap skin paddle was extended 3 cm posteriorly to the middle thigh (group 1). For the next 20 flaps (group 2), the posterior tip was limited to this line, whereas more fat was recruited inferiorly. In the four cases of group 3, the skin flap was extended posteriorly with a second vascular pedicle from the profunda artery perforator (PAP) flap. The weights and the dimensions of the flaps, operating durations, and postoperative complications of the entire series were analyzed. Groups 1 and 2 were statistically compared. Results: Flap complications were statistically more frequent in group 1 compared with group 2 (45 vs. 0%, P  = 0.0012); 40% posterior flap tip necrosis was observed in group 1. Conversely, donor site complications were statistically more frequent in group 2 than in group 1 (40 vs. 5%, P  = 0.019) with 35% inner thigh dehiscence. In the TMG with extended PAP flap group, the operating duration was 77 min longer compared with the rest of the series with no donor site complications. In one case, limited necrosis occurred at the anterior skin tip. Conclusions: Harvesting the posterior portion of the TMG up to the middle of the posterior thigh may lead to partial flap necrosis. Extending subcutaneous fat removal under the inferior skin incision may increase the risk of donor site complications. Adding a second vascular pedicle from the PAP flap may improve posterior TMG tip perfusion at the expense of a longer operation. © 2015 Wiley Periodicals, Inc. Microsurgery 36:42–48, 2016.